Negative Influences of Learning Piano on School Students: Learn piano music，Negative impact, Cultural development,Teacher teaching - Na, Zhang; Fernando, Yudi (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
Piano has been integrated into the cultural and historical development of human existence because of the role it plays in shaping the life of people especially the upcoming generation. Songs that have been passed down through generations are an important part of human life. It is easier for students to become overly excited by listening and learning piano because students tend to be more emotional. But this can have a negative impact on Teddy in a variety of different ways. Because of the excessive excitement, they have less motivation to study, and it encourages them to form lifestyles that are not appropriate for them. Even though it can bring students together and bring a large community closer together, learning to play the piano can lower a person's social status later in life. This is true even though learning to play the piano can bring students together. The singing style is completely composed in a rural style, and this is the reason for this difference. The existence of folklore acts as a barrier that prevents the development of a specific subculture. In addition to this, it has the potential to change people's perspectives on a diverse range of things and forms. When one listens to music, neural responses in the brain are triggered that are very similar to those that are triggered when one speaks. On the other hand, listening to music has been shown to stimulate the part of the brain that is accountable for the emergence of unwelcome feelings. This is the primary reason why taking piano lessons can have such a detrimental effect on a student's life. The study further suggested more research on the particular areas that are more detrimental to student life in piano so that they can be improved as piano is also important in other aspects of human development.